2013
DOI: 10.1007/s10827-013-0481-5
|View full text |Cite
|
Sign up to set email alerts
|

How well do mean field theories of spiking quadratic-integrate-and-fire networks work in realistic parameter regimes?

Abstract: We use mean field techniques to compute the distribution of excitatory and inhibitory firing rates in large networks of randomly connected spiking quadratic integrate and fire neurons. These techniques are based on the assumption that activity is asynchronous and Poisson. For most parameter settings these assumptions are strongly violated; nevertheless, so long as the networks are not too synchronous, we find good agreement between mean field prediction and network simulations. Thus, much of the intuition deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Fig 4 (B) shows that the mean field approximation for the firing rates of neurons in the network matches simulations with great precision for a wide range of N and K , and that the average firing rates are independent of N and change monotonically with K , as expected from previous work [16, 47]. Later, we will make use of the quantities μ E , I and derived in Eq (6) to outline the difference between network and MF responses for fixed stimuli.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…Fig 4 (B) shows that the mean field approximation for the firing rates of neurons in the network matches simulations with great precision for a wide range of N and K , and that the average firing rates are independent of N and change monotonically with K , as expected from previous work [16, 47]. Later, we will make use of the quantities μ E , I and derived in Eq (6) to outline the difference between network and MF responses for fixed stimuli.…”
Section: Methodssupporting
confidence: 80%
“…This dip occurs because QIF dynamics produce a relative refractory period, leading to typical Fano Factors lower than one (between 0.77 and 1 in all of our simulations). This is refractory period can be regarded as a realistic feature; in any case, the use of assumption (ii) still leads to correct estimates for our dynamical regime, as was also observed in [47]. …”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Current-based LIF models are popular because of their relative simplicity (see e.g., Brunel, 2013) and they have the key advantage of facilitating the derivation of analytical closed-form solutions. Thus current-based synapses are convenient for developing mean field models (Grabska-Barwinska and Latham, 2013), event-based models (Touboul and Faugeras, 2011), or firing rate models (Helias et al, 2010; Ostojic and Brunel, 2011; Schaffer et al, 2013), as well as in studies examining the stability of neural states (Babadi and Abbott, 2010; Mongillo et al, 2012). Moreover, current-based models are often adopted, because of their simplicity, to investigate numerically network-scale phenomena (Memmesheimer, 2010; Renart and Van Rossum, 2012; Gutig et al, 2013; Lim and Goldman, 2013; Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The very first studies in neuroscience demonstrated analytically that the mean-field approximation was valid for homogenous neural networks when the numbers of neurons tend to infinity (Amari, 1972;Amari et al, 1977). Ever since, numerous studies have analysed the mean-field in neural networks under diverse conditions such as in finite neural networks (Mattia and Del Giduice, 2002;Touboul and Ermentrout, 2011), with different connectivity patterns (Cessac and Vieville, 2013;Moynot and Samuelides, 2002;Samuelides and Cessac, 2007;Brunel and hakim, 1999;Cessac, 1995), using different single-cell neuronal models (Abbot and Vreeswijk, 1993;Cessac, 2008;Treves, 1993)), using realistic parameter regimes (Grabska-Barwinska and Latham, 2013), or as a function of time (Molgedey et al, 2013;Moynot and Samuelides, 2002), the so-called dynamic mean-field approaches.…”
Section: Introductionmentioning
confidence: 99%